THE VOCAL SCORE IN THE OPERA “THE LYING WOLF” BY ZLATA TCACH - GUŢANU STOIAN, Luminiţa (Studia Universitatis Babes-Bolyai Musica, 2016)
This study aims at emphasizing the composer’s ability to attain a musical construction for each of the opera’s characters.We will notice that, in this opera, Zlata Tkach (also spelled “Tcaci”) uses both traditional, formal structures, such as the aria, arioso, as well as less traditional ones – the song, using, in all of them, three facets of the relation between text and melody, starting with the prevalence of the text, often shifting to a primordially of the melody, but still inclining, most of the time, toward an equivalence between the text and its musical pillar. As regards the makeup of the musical discourse, the author proceeds in a detailed manner, with each role, and the melodic ideas that she constructs are subjected to a unitary, evolving vision.